Who pays for standardised testing? A cost-benefit study of mandated testing in three Queensland secondary schools. Issue 3 (3rd May 2016) - Carter, Merilyn Gladys; Klenowski, Valentina; Chalmers, Christina
Abstract : This paper reports on an Australian study that explored the costs and benefits of the National Assessment Programme, Literacy and Numeracy (NAPLAN) testing, both tangible and intangible, of Year 9 students in three Queensland schools. The study commenced with a review of pertinent studies and other related material about standardised testing in Australia, the USA and UK. Information about NAPLAN testing and reporting, and the pedagogical impacts of standardised testing were identified, however little about administrative costs to schools was found. A social constructivist perspective and a multiple case study approach were used to explore the actions of school managers and teachers in three Brisbane secondary schools. The study found that the costs of NAPLAN testing to schools fell into two categories: preparation of students for the testing; and administration of the tests. Whilst many of the costs could not be quantified, they were substantial and varied according to the education sector in which the school operated. The benefits to schools of NAPLAN testing were found to be limited. The findings have implications for governments, curriculum authorities and schools, leading to the conclusion that, from a school perspective, the benefits of NAPLAN testing do not justify the costs.